Analisis Vegetasi Keanekaragaman Tumbuhan Perdu di Bantaran Sungai Sebagai Materi Unit Pembelajaran Keanekaragaman Hayati - Adib Syuja Dewa; Nirwana Nirwana; Bhakti Karyadi; Deni Parlindungan; Ariefa Primairyani; Rendi Zulni Ekaputri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the diversity of shrubs along the banks of the Rindu Hati River in Central Bengkulu, the output of which will be a Learning Unit Book (BUP). The research method is research and development limited to needs analysis and design framework. In this study, the location determination used the porposive sampling technique based on the presence of shrubs which were considered to represent places in the longing liver river. The results showed that the number of shrub species on the banks of the Miss Hati River found was 230 of 21 species of shrubs. The diversity index value (H') ranges from 2.311-2.511 which is included in the medium category, the evenness index (E) ranges from 0.759-0.83 which is included in the high category, and the dominance index (C) ranges from 0.09-0.1065 which is included in the high category. low. In conclusion, from this data it is necessary to develop a teaching material that can facilitate students in learning which contains a diversity of shrubs which is facilitated by teachers and students in facilitating learning to classify living things. The teaching material is in the form of a learning unit book (BUP). Keywords: Teaching Materials, Learning Unit Books, Shrubs, Sungai Rindu Hati